Predictive markers in lung cancer: a few hints for the practicing pathologist - BARBARESCHI, M.; BARBERIS, M.; BUTTITTA, F.; DOGLIONI, C.; FIORENTINO, M.; FONTANINI, G.; FRANCO, R.; MARCHETTI, A.; ROSSI, G.; TRONCONE, G. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
This review article highlights some important points in the evolving area of predictive biomarkers determination in non-small-cell lung cancer toward standardization of testing practices, including EGFR mutations, ALK and ROS1 rearrangements and immunohistochemical expression of PD-L1. Considerations for selecting appropriate populations for molecular testing, and emergence of other targetable molecular alterations are also discussed.